THE INFLUENCE OF TRAINING AND DEVELOPMENT TOWARDS EMPLOYEE PERFORMANCE AND TURNOVER INTENTION AMONG MILLENNIALS IN MALAYSIA - Shan Ling Yek; Yen Ping Ki; Agnes Siew Siang Lim (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
The COVID-19 pandemic has negatively impacted Malaysian employees’ performance and turnover intention. Recent research indicates that employees, particularly millennials, often struggle to perform at their highest potential during their early employment stages. Many organizations face financial constraints due to the impact of the COVID-19 pandemic, limiting the scope and effectiveness of the training they can provide. This study investigates the impact of training and development on employee performance and turnover intention among millennials in Malaysia. The partial least squares structural equation modelling (PLS-SEM) was utilized to analyse the data obtained from 307 Malaysian millennial employees. The findings show that the respondents have a high level of training and development satisfaction, a medium level of employee performance, and a low turnover intention. The findings also reveal a weak but significant positive relationship between training and development and employee performance. In addition, the results show a significant negative relationship between training and development, employee performance, and turnover intention. This research provides more in-depth insights that can help Malaysian organizations and managers increase employee performance and retention using Human Capital Theory.